Evolution and transformation dynamics of rangeland in Moroccan north Atlasic plains and plateaux: Rhamna’s case - El Koudrim M.; Ouabbou H.; El Hilali S. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Rhamna region is an agro-pastoral zone characterized by an arid climate. It is part of pastoral ecosystems classified as moderately degraded in Morocco. The objective of this research is to determine the dynamics of this ecosystem over time by integrating the effects of climate change. The dynamics of land-use change was apprehended by a study of multi-date remote sensing of satellite images (1987 and 2017). The diachronic study of land use in Rhamna shows a clear regression of pastoral areas in favor of cultivated land and often gives way to completely bare land. Critical regression of vegetation cover is mainly due to increasing pressure. But climate change has aggravated the situation in recent decades. Long-term analysis of climate data shows that one year out of two is considered agronomically dry. Other environmental degradation factors stem from current changes in pastoral society. Indeed, the last sequence of dry years has led to a massive use of concentrate feeds. Cereal cultivation, although not a new phenomenon in the region, has reached alarming proportions.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)